Biomechanical comparison of various bone reduction forceps in interfragmentary compression and area of compression in an experimental model of canine lateral humeral condylar fractures - Madison Baskette; Cássio Ricardo Auada Ferrigno (PLoS ONE, 2025)
Objective To compare contact area and interfragmentary compression generated by Vulsellum forceps, Patellar forceps, Kyon FineTouch forceps, point-to-point forceps with soft-locking mechanism, and point-to-point forceps with speed-locking mechanism in simulated lateral humeral condylar fractures in canine cadavers. Study design Ex-vivo biomechanical study. Materials and methods Seven cadaveric canine humeri with simulated lateral humeral condylar fractures were used in this study. A stress-sensitive film was placed at the fracture gap and five different bone reduction forceps were used to reduce the fractures to their maximum pressure before failure occurred. The compression and interfragmentary compression area were recorded during the entire compression interval and compared after the pressure had reached a plateau. Results Patellar forceps generated the highest interfragmentary compression, followed by Vulsellum forceps. Compression generated by both the Patellar and Vulsellum forceps were significantly higher than point-to-point forceps with soft-lock, point-to-point forceps with speed lock, and Kyon forceps (P = 0.0008, 0.0084). No statistically significant difference was observed in the areas of compression among all forceps types. Conclusion Patellar and Vulsellum forceps generate a greater interfragmentary compression compared to Kyon FineTouch forceps and point-to-point forceps with both speed and soft-locking mechanisms in this experimental lateral condylar fracture model.